Configuration of factories and technical processes: which role plays knowledge modelling? - Landherr, M.; Constantinescu, C. C. (НТУ "ХПИ", 2011)
The paper presents our first research steps aiming at the development of a methodology for knowledge-based configuration of factories and technical processes. The complex task of configuration is firstly introduced and the need for embedding knowledge as an enabling technology is pointed out. The requirements analysis illustrated by a motivation scenario is followed by the analysis of state-of-the-art information and communication technologies and their particular applicability for the configuration of production facilities. The paper concludes with the selection of suitable enabling technologies and the roadmap of future activities.

Статья представляет наши первые исследовательские шаги, преследующие цель развития методологии для построения основывающейся на банке знаний конфигурации предприятия и промышленных процессов. Обращено внимание на необходимость внедрения впервые рассматриваемой комплексной задачи конфигурации баз знаний как высокоэффективной технологии. Анализ необходимых условий проиллюстрирован мотивационным сценарием, вытекающим из анализа реальной информации, взаимосвязей технологий и их приспособляемости для перекомпоновки производственных мощностей. Статью завершает выбор подходящих к применению технологий и дорожная карта будущей активности.
Конфигурация предприятия и промышленных процессов: какую роль играет моделирование банка знаний?
Keywords: knowledge-based configuration; technical processes; communication technologies; планирование производств; модель БЗ